2006
DOI: 10.1165/rcmb.2005-0166oc
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Induces Airway Smooth Muscle Hypertrophy

Abstract: Although smooth muscle hypertrophy is present in asthmatic airways, little is known about the biochemical pathways regulating airway smooth muscle protein synthesis, cell size, or accumulation of contractile apparatus proteins. We sought to develop a model of airway smooth muscle hypertrophy in primary cells using a physiologically relevant stimulus. We hypothesized that transforming growth factor (TGF)-␤ induces hypertrophy in primary bronchial smooth muscle cells. Primary human bronchial smooth muscle cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 41 publications
8
94
0
Order By: Relevance
“…However, protein synthesis and ␣-actin expression induced by the pleotrophic growth factor TGF-␤ were not blocked by either GSK-3␤A9 or eIF2B siRNA, suggesting that, in the context of TGF-␤ treatment, an alternative pathway or pathways are sufficient for the hypertrophic response. As noted above, besides phosphorylation and inhibition of GSK-3␤, TGF-␤ treatment is also followed by phosphorylation of 4E-BP, which facilitates eIF4E-dependent translation of 7-methylguanine-capped mRNAs (27). Overexpression of AA-4E-BP, a nonphosphorylatable mutant, inhibited TGF-␤-induced airway smooth muscle hypertrophy.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, protein synthesis and ␣-actin expression induced by the pleotrophic growth factor TGF-␤ were not blocked by either GSK-3␤A9 or eIF2B siRNA, suggesting that, in the context of TGF-␤ treatment, an alternative pathway or pathways are sufficient for the hypertrophic response. As noted above, besides phosphorylation and inhibition of GSK-3␤, TGF-␤ treatment is also followed by phosphorylation of 4E-BP, which facilitates eIF4E-dependent translation of 7-methylguanine-capped mRNAs (27). Overexpression of AA-4E-BP, a nonphosphorylatable mutant, inhibited TGF-␤-induced airway smooth muscle hypertrophy.…”
Section: Discussionmentioning
confidence: 91%
“…More recently, cardiotrophin (CT)-1, a member of the IL-6 superfamily present in human lungs, has been shown to induce protein synthesis and cell enlargement, but not DNA synthesis, in cultured human bronchial smooth muscle cells (21) and guinea pig airway explants (22). In addition, we showed that transforming growth factor (TGF)-␤, a proasthmatic cytokine (23)(24)(25)(26), increased human bronchial smooth muscle cell size, protein synthesis, expression of ␣-smooth muscle actin and smooth muscle myosin heavy chain (smMHC), formation of actomyosin filaments, and cell shortening to acetylcholine (27). Further, TGF-␤ induced the phosphorylation of eIF-4E-binding protein (4E-BP), and inhibitors of 4E-BP phosphorylation blocked TGF-␤-induced ␣-actin expression and cell enlargement, suggesting that eIF4E-, cap-dependent translation is necessary for TGF-␤-induced hypertrophy.…”
mentioning
confidence: 91%
“…TGF-b1 increases contractile protein expression in HASM, fibroblasts, and myofibroblasts. TGF-b1 induces the expression of SM22, calponin, a-SMA, MLCK, and Ca 21 pathway proteins in HASM cells, subsequently mediating enhancements in cell stiffness, actin-cytoskeleton reorganization, and contractility (87,104,105). In addition, mast cell-derived TGF-b1 may modulate the phenotype of HASM cells, promoting their differentiation into a more contractile phenotype and subsequently enhancing agonist-induced contraction (106).…”
Section: Contraction Cell Shortening and Cytoskeletal Motorsmentioning
confidence: 99%
“…Supports for this contention are accumulating. Cytokines such as interleukin (IL)-1 (11,92,200,250), tumor necrosis factor (TNF) (4,7,167,168,172,191,193,200,227), the combination of TNF and IL-1 (90,92), IL-13 (41,62,80,228), IL-5 (93, 250), IL-10 (79), granulocytemacrophage colony-stimulating factor (GM-CSF) (94), interferon (IFN) (5), leukemia inhibitory factor (LIF) (63,119) and transforming growth factor (TGF) (75,255), as well as the protease -tryptase (212,255) were shown to increase ASM contractility. In turn, the effect of these mediators is not always direct.…”
Section: Inflammatory Cells and Moleculesmentioning
confidence: 99%
“…The molecular mechanisms governing the transformation of ASM into a hypercontractile phenotype may differ from one inflammatory mediator to another. In the case of TGF, increased expression of the contractile protein -SMA and actin filamentogenesis have been proposed (75,76). On the other hand, many inflammatory mediators increase ASM contractility through shared mechanisms related to alterations in calcium handling; either by Ca 2+ sensitization via the Rho-ROCK pathway or by increasing the intracellular mobilization of Ca 2+ via the CD38/cADPR/RyR pathway (both briefly described below and illustrated in Figure 4).…”
Section: Inflammatory Cells and Moleculesmentioning
confidence: 99%